Commentary: Developments and reforms in science education for improving the quality of teaching and research - Treagust, David; Tsui, C. (2016)
Reviewing colleagues’ work and providing a review, a commentary, or reflections is always a privilege because it enables the reader to be more aware of his or her own research contributions. The reader may provide critical and constructive comments as in the case of a journal manuscript submitted for consideration or as in the case of this chapter to reflect how the reading relates to the reviewers’ knowledge and experiences and then comment. In this chapter, we comment on some aspects—it is not possible to comment on all—and reflect upon the chapter authors’ work from Mainland China, Lebanon, Macau, Malaysia, and Mongolia about science education research and practice in their countries/regions.